Application of infrared to biomedical sciences - Ng, Y. K. Eddie; Etehadtavakol, Mahnaz (Springer, 2017)
The book covers the latest updates in the application of infrared to biomedical sciences, a non-invasive, contactless, safe and easy approach imaging of skin and tissue temperatures. Its diagnostic procedure allows practitioners to identify the locations of abnormal chemical and blood vessel activity such as angiogenesis in body tissue. Its non-invasive approach works by applying the technology of the infrared camera and state-of-the-art software, where high-resolution digital infrared imaging technology benefits highly from enhanced image production, standardized image interpretation protocols, computerized comparison and storage, and sophisticated image enhancement and analysis. The book contains contributions from global prominent scientists in the area of infrared applications in biomedical studies. The target audience includes academics, practitioners, clinicians and students working in the area of infrared imaging in biomedicine.
Includes index.
Keywords: Medical thermography.; elektronické knihy; electronic books